IPTEKS PERLAKUAN ASET TETAP TERHADAP DINAS PUPRD PROVINSI SULAWESI UTARA - Timang, Agusta Komeshky; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Government regulations regarding fixed assets have been stated in Government Regulation Number 71 of 2010 concerning PSAP of fixed assets where fixed assets are important things that must be considered in the regional government service in this case the North Sulawesi Regional Public Spatial Planning service. Fixed assets are tangible assets in the form of buildings, equipment, land, machinery, and vehicles. In this case, the accounting treatment for fixed assets will be discussed in the Regional Spatial Planning Public Works Agency. From the existing studies it is used to describe something data or facts that exist or are clearly found. From the theory of previous research, it can be seen that the recognition of fixed assets in the Manado PUPRD Office is appropriate The PUPRD Service has used fixed assets in accordance with applicable government regulations because fixed assets have been repaired by the PUPRD Service by transferring unused fixed assets to other fixed assets posts.Keywords : fixed assets and psap no. 7